Molecular assembly of metallacarboranes in water: light scattering and microscopy study - Matejícek, Pavel; Cígler, Petr; Procházka, Karel; Král, Vladimír (Langmuir, 2006)
Polyhedral metallacarboranes are used mainly as ion-pairing agents and recently have been recognized as potent inhibitors of HIV protease. They are characterized by exceptional hydrophobicity, rigid geometry, delocalized negative charge, ion-pairing behavior, and strong acidity of their conjugated acids. The completely novel phenomenon, association of these promising pharmaceutical tectons in aqueous solutions, is described here. The behavior of two structural types of metallacarboranes, [bis(1,2-dicarbollide)cobaltate(1-)] and bis[(3)-1,2-dicarbollylcobalt]-(3,6)-1,2-dicarbacanastide(2-)], in aqueous solution was studied by a combination of static and dynamic light scattering and microscopy methods. Spherical aggregates with radii of ca. 100 nm and fairly monodisperse nanostructures were found in aqueous solutions. The behavior of nanoaggregates is fairly complex and depends on the concentration and aging of the solutions. The particles are stabilized in the solution by counterions. The formation of larger clusters upon dilution of bis(1,2-dicarbollide)cobaltate(1-) solutions was observed. The secondary aggregation can be suppressed by addition of NaCl. Gel permeation chromatography measurements of sodium bis(1,2-dicarbollide)cobaltate(1-) show that the majority of matallacarborane molecules form nanoaggregates and only a small amount of the metallacarborane remains molecularly soluble or forms small oligomers.